Self-healing of Cementitious Structures through Biomineralisation by Using Fungal System - Yashika (Thapar Institute of Engineering and Technology, 2025)
Micro-cracks in cement-based materials significantly reduce their durability by allowing moisture and aggressive agents to penetrate, eventually compromising structural performance. This research explores the use of urease-positive fungal strains to enable autonomous crack healing in concrete via microbial-induced calcium carbonate precipitation (MICP). Two healing strategies were employed: direct injection of fungal hyphae into cracks and a novel approach where fungal spores were incorporated with fly ash to act as a carrier and filler medium. After introducing artificial cracks in mortar specimens, the fungal healing agents were applied, followed by nutrient spraying to encourage fungal proliferation and calcite precipitation within the cracks. The healing performance was evaluated through compressive strength tests, enzymatic urease activity measurement, calcium ion quantification, and Scanning Electron Microscopy (SEM) analysis. The specimens treated with spore-fly ash composites showed superior crack sealing efficiency and maximum strength regain, attributed to the combined pozzolanic reaction and biologically driven mineral deposition. This study validates fungal biomineralization as a viable, eco-friendly self-healing technique, offering a sustainable alternative to traditional repair methods for enhancing the longevity and durability of cementitious infrastructure.
Keywords: Bioconcrette; Self-healing; Compressive strength; Cladosporium xanthochromaticum; Urease; Crack healing